Pengaruh Persepsi Risiko, Pengetahuan, Dan Motivasi Terhadap Minat Investasi Mahasiswa Di Pasar Modal: (Studi Kasus pada Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Bina Sarana Informatika Program Studi Akuntansi) (Jurnal Kendali Akuntansi, 2023)
This study aims to determine the effect of risk perception, knowledge, and motivation on students' interest in investing in the capital market (a case study on undergraduate students at Bina Sarana Informatics University, Major Accounting). This research method uses a quantitative approach with technical multiple linear regression analysis processed using SPSS. The data collection technique is by distributing questionnaires to 100 students as respondents via the google form. The results of the study show that knowledge and motivation have a significant effect on investment interest, while risk perception has no effect on student investment interest in the capital market. Simultaneously risk perception, knowledge, and motivation have a positive and significant effect on students' interest in investing in the capital market.